Advocacy, social control, and the criminalisation of same-sex relationships : the evolution and enforcement of ‘anti-gay laws’ in Nigeria - Viljoen, Frans (University of Pretoria, 2021)
Thesis (LLD)--University of Pretoria, 2020.